Integrasi Nilai-Nilai Islam dalam Kurikulum Pendidikan Guru Madrasah Ibtidaiyah di STAI DDI Pangkep: Integration of Islamic Values in the Elementary Madrasah Teacher Education Curriculum at STAI DDI Pangkep - Fahirah; Majid, Abdul; Anggriani Amir (Universitas Muhammadiyah Palu, 2025)
The integration of Islamic values into the curriculum of the Madrasah Ibtidaiyah Teacher Education (PGMI) program plays a strategic role in shaping students’ professionalism. This study aims to analyze how Islamic values are implemented in the PGMI curriculum at STAI DDI Pangkep and their impact on students’ academic, pedagogical, and Islamic character competencies. The research employed a qualitative descriptive method with data collection techniques including literature review, classroom observation, and interviews with lecturers and students. The findings indicate that the integration of Islamic values is carried out through the design of religion-based courses, contextual learning strategies that connect theory to practice, and extracurricular activities that support the internalization of Islamic values. This implementation effectively enhances students’ professionalism, particularly in discipline, responsibility, lesson planning skills, and ethical and social behavior. The study emphasizes the importance of developing a holistic, adaptive, and innovative curriculum so that PGMI graduates are not only academically competent but also possess strong Islamic character, are prepared to face educational challenges, and can serve as role models for Madrasah Ibtidaiyah students.